The Welcome Asians: the Japanese in Mexico, 1897–1910. Issue 3 (2nd July 2016) - Peddie, Francis
Abstract : This article focuses on the development of diplomatic relations between Japan and Mexico in the second half of the nineteenth century, culminating in the Treaty of Friendship, Commerce and Navigation between the two nations in 1888, and the subsequent effect the positive relationship between the two nations had on Japanese immigration to Mexico. Based on a spirit of reciprocity and equal status, the treaty resulted in a favourable opinion regarding Japan and the Japanese in Mexico that had a direct influence on the way in which Japanese immigrants to Mexico were viewed and treated, which stands in sharp contrast to the experiences of other Japanese migrant communities in the Americas. Viewed as agents of modernization, Japanese immigrants were welcomed or viewed neutrally by Mexican government officials and average citizens. The article also explains why, despite this positive relationship, Mexico never became a large-scale destination for Japanese immigration.